Assédio moral e a reparação da dignidade do trabalhador - Ferreira, Marina Cláudia Caixeta (2012)
The concern with a healthy work environment in which the dignity of workers is recognized as a result has had a greater emphasis to the study of bullying. This research aimed to analyze this social phenomenon in the light of the principle of human dignity, especially drawing theoretical foundations for analyzing the repair of damage resulting from the practice harassing, seeking evidence to measure parameters of the \"quantum\" indemnity arising from the humiliation and constraint on harvest labor. The present study is justified by the psychological terror imposed by bullying in the social environment, family, student and under the Labor Law. The psychological abuse can be so severe that the victim physically and mentally ill, even sometimes to death. In addition, the parameters for measuring the repairability of moral pain reveal themselves indispensable, as it claims with well-differentiated values have been refereed by the labor courts. For this study, was carried out theoretical research, compiling and reviewing material doctrinal literature concerning the proposed themes. In the methodological procedure, we adopted the systematic method. Elected to documentary research, focusing on law and jurisprudence, especially near the Superior Labor Court, which also investigated the views of Courts of Appeal regarding the proposed theme. It was found by sampling the Brazilian labor law has been taking so dominant, financial compensation as a remedy of bullying, following a trend of more economically developed countries. It was concluded that the Superior Labor Court held all decisions of the second degree, in particular, mentioning explicitly the criteria of reasonableness and proportionality, inscribe in Article 5, Paragraph V of the Constitution, as guidelines for measuring the quantum severance of harassing practice.